Theatre/Novel: Titus n’aimait pas Bérénice by Nathalie Azoulai (prix Médicis 2015) (Itinera, 2019)
A novelistic rewriting of Racine’s tragedy, which projects the character Berenice into our time while killing Titus, this novel by Nathalie Azoulai lends itself to a narratological analysis that describes the different modalities of the intermedial transposition here at work. Beyond this formalist approach, however, it is worth considering the meaning of this transmodalisation: a tribute from the novel to the theatre, this story is above all a romanticized biography of Racine and thus plays on genres. But the interlocking of the two levels of fiction and the hypertrophy of metapoetic discourse are here lures that mask the reverence of postmodernity to classicism, opposing the majesty of style to the sloppy of contemporary autofiction. Racine, Nathalie Azoulai, intermedial transposition, transmodalisation